Why do the outward FDI patterns of China's state-owned enterprises differ from those of private companies? - Zhi, Li. (2010)
Since China's implementation of the "opening up and reform" in 1979 led by Deng Xiaoping, and the establishment of the first SEZ (Special Economic Zone) - Shenzhen in the early 19807s, huge foreign capital inflows and the active operations of foreign-invested firms have greatly affected China's institutional environment, and intensified market competition. To a large extent, the inward Foreign Direct Investment (FDI) also affects and hinders the development of local brands that are unable to compete with established foreign brands. Hence, the Chinese government has adopted a "going global" policy as a means of building up national champion brands in the global market. Both state-owned and private-owned enterprises are active in this course of "going-out". However, their patterns of outward FDI differ in several aspects. The key reason accounting for the differences of outward FDI patterns is that the state-owned companies, controlled or backed by the central government directly or indirectly, are influenced by political interests and policies enforced by Beijing government to achieve the long-term national goal, while the private-owned companies are primarily profit-oriented when they invest abroad.